1995
DOI: 10.2307/1243547
|View full text |Cite
|
Sign up to set email alerts
|

Legal Status and Earnings of Agricultural Workers

Abstract: Agricultural workers who work in the United States earn 15% more on average than do undocumented workers. These earnings differentials vary substantially with demographic characteristics. For example, much of the weekly earnings loss from not having legal status can be offset by language ability. Most of the earnings differential is due to wage differentials rather than hours differentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…They were younger, had been employed in the US and had worked as a farmworker for fewer years, were less likely to be married and less likely to be accompanied by a household member than documented farmworkers [Villarejo et al, ]. Lower wages, in the range of 10–15% lower for undocumented agricultural workers compared with documented workers have been reported in other farmworker populations [Isé and Perloff, ; Iwai et al, ]. Undocumented status can be viewed as a social determinant of occupational health and safety because of the role it plays in the risks workers face at work and on their ability to respond to those risks [Flynn et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…They were younger, had been employed in the US and had worked as a farmworker for fewer years, were less likely to be married and less likely to be accompanied by a household member than documented farmworkers [Villarejo et al, ]. Lower wages, in the range of 10–15% lower for undocumented agricultural workers compared with documented workers have been reported in other farmworker populations [Isé and Perloff, ; Iwai et al, ]. Undocumented status can be viewed as a social determinant of occupational health and safety because of the role it plays in the risks workers face at work and on their ability to respond to those risks [Flynn et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…4 This setup is similar to that employed byHazari and Sgro (2003). Work byRivera-Batiz (1999) andIse and Perloff (1995) among others has shown that in the United States undocumented immigrants earn lower wages than statistically similar documented immigrants…”
mentioning
confidence: 68%
“…Gaytan-Fregoso and Lahiri (2000) incorporate both border surveillance and domestic enforcement and find that these policies lower (augment) the host (source) country's welfare. 5 Isé and Perloff (1995) provide evidence that undocumented workers earn less than legal workers and this wage gap can be reduced by improving immigrants' skills such as language ability. Devadoss and Luckstead (2008) find, in California vegetable production, one new immigrant displaces only 0.0123 domestic workers and has an inconsequential impact on native wage rates, but augments vegetable production by $23,457 and the contribution of skilled workers, material inputs 4 The H-2A programme is very expensive as it requires producers to incur administrative costs related to visa permits, recruitment activities, housing accommodation and transportation (round-trip tickets from Mexico and local rides to work sites, grocery stores and religious locations).…”
Section: Past Studiesmentioning
confidence: 99%